Forage sorghum yield as a function of nitrogen rates and cut management (Research, Society and Development, 2021)
Forage sorghum is a plant with high potential for the Brazilian Midwest, especially because it is considered tolerant to adverse conditions and the high capacity of tillering and regrowth of the ratoons after being cut for silage. The objective of this work was to evaluate the influence of nitrogen (N) doses and cutting management on yield of the forage sorghum hybrid Agri 002E, cultivated in the central region of Mato Grosso do Sul. The design was a randomized block design, with four replications, in a scheme factorial 2x4 and the factors were: two cutting times and four doses of N in topdressing (0, 50, 150 and 200 kg.ha-1). The times of first cutting (FC) were 63 (FC63) and 97 (FC97) days after sowing (DAS). The experiment was repeated after FC until a second cut (SC), at 160 DAS. Plant yeld was evaluated right after each cut. Both cuts were considered as cutting management: 1. FC63, followed by SC 97 (FC63+SC97) and 2. FC97, followed by SC 63 (FC97+SC63). Regardless of the period of permanence of the plants in the field, sorghum yeld was higher in the first cut and the effect of N doses on yield was restricted to the 97-day period preceding SC. The dry matter content ranged from 34.7 to 38.5%. FC97+SC63 was more efficient as it provided the highest yields of fresh (96.6 t.ha-1) and dry (37.9 t.ha-1) matter.